1998
DOI: 10.1590/s0104-42301998000300010
|View full text |Cite
|
Sign up to set email alerts
|

Ressecção cirúrgica de metástases pulmonares: estudo prospectivo em 182 pacientes

Abstract: RESUMO -OBJETIVO. O presente estudo visa ava UNITERMOS:Metástases. Pulmão. Prognóstico. Cirurgia. INTRODUÇÃOO diagnóstico de metástases pulmonares em pacientes portadores de tumores malignos é considerado um sinal de doença sistêmica e por muitos anos caracterizado como fase terminal da evolução do paciente. O tratamento convencional de pacientes com metástases pulmonares consiste em quimioterapia, hormonioterapia e, por vezes, radioterapia. Os resultados observados nos diferentes estudos apresentam resposta o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 26 publications
1
9
2
8
Order By: Relevance
“…We understand this finding to mean that the need for neoadjuvant and adjuvant treatment indicates disease in more advanced stages and weakness associated with sequential multimodal treatment. However, this finding is in disagreement with the results reported by Younes et al,( 8 ) who found a significant improvement in survival in the group of patients who underwent chemotherapy/radiotherapy, as well as with the finding of an absence of significant differences between these two groups in the main studies( 20 - 22 ) reviewed in the meta-analysis by Pfannschmidt,( 15 ) which leads us to agree with the opinion of those authors who claim that the different protocols for the different types of primary tumor may hinder the understanding of the true impact on the survival of patients undergoing complementary treatment.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…We understand this finding to mean that the need for neoadjuvant and adjuvant treatment indicates disease in more advanced stages and weakness associated with sequential multimodal treatment. However, this finding is in disagreement with the results reported by Younes et al,( 8 ) who found a significant improvement in survival in the group of patients who underwent chemotherapy/radiotherapy, as well as with the finding of an absence of significant differences between these two groups in the main studies( 20 - 22 ) reviewed in the meta-analysis by Pfannschmidt,( 15 ) which leads us to agree with the opinion of those authors who claim that the different protocols for the different types of primary tumor may hinder the understanding of the true impact on the survival of patients undergoing complementary treatment.…”
Section: Discussioncontrasting
confidence: 97%
“…In the study by Pfannschmidt et al.,( 15 ) the perioperative mortality rate ranged from 0% to 2.02%, whereas, in the study conducted in Brazil by Younes et al,( 8 ) the rate was 0.4%. These results are in good agreement with the value of 1.9% found in the present study, showing the safety of the method.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations